2004
DOI: 10.3402/meo.v9i.4347
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Views of Medical Students toward Science and Pseudoscience

Abstract: Medical students' attitudes toward science are generally not favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…According to Miller (2010), the most reliable predictors of scientific literacy were attending at least three courses of science during the undergraduate programme, followed by obtaining a college degree and staying in touch with scientific news through media sources. In line with these findings, research showed that medical students demonstrate the same low level of scientific literacy, albeit the importance of scientific reasoning in healthcare (Peña, 2004). These systematic findings of low levels of scientific literacy have led to what has come to be termed as "the deficit model" (Sturgis & Allum, 2004).…”
Section: Scientific Literacy In Higher Educationmentioning
confidence: 82%
“…According to Miller (2010), the most reliable predictors of scientific literacy were attending at least three courses of science during the undergraduate programme, followed by obtaining a college degree and staying in touch with scientific news through media sources. In line with these findings, research showed that medical students demonstrate the same low level of scientific literacy, albeit the importance of scientific reasoning in healthcare (Peña, 2004). These systematic findings of low levels of scientific literacy have led to what has come to be termed as "the deficit model" (Sturgis & Allum, 2004).…”
Section: Scientific Literacy In Higher Educationmentioning
confidence: 82%
“…The studies with undergraduate and post-graduate levels showed some problematic situations about attitudes and understandings regarding to science in medical education. Although they took these courses, studies showed that medical students had positive attitudes toward pseudoscience including medical concern such as parapsychology, therapeutic touch, homeopathy and alternative medicine [9,10]. In addition, Pena and Paco showed majority of medical students did not read or follow any sources related to science for a five-year long period and did not know definition and aspects of science [10].…”
Section: Importance Of Biological Literacy and Nos For Graduate Medicmentioning
confidence: 99%
“…Although they took these courses, studies showed that medical students had positive attitudes toward pseudoscience including medical concern such as parapsychology, therapeutic touch, homeopathy and alternative medicine [9,10]. In addition, Pena and Paco showed majority of medical students did not read or follow any sources related to science for a five-year long period and did not know definition and aspects of science [10]. Again, Pena, Paco and Peralta found that no physicians knew the pre-assumptions of science and majority of them did not know definition of scientific theory [11].…”
Section: Importance Of Biological Literacy and Nos For Graduate Medicmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical thinking skills and dispositions are generally considered desirable outcomes of the educational process. Beliefs in the paranormal and pseudoscience may indicate a decline in scientific literacy and critical thinking, their prevalence among university students has motivated some to affirm that education in industrialized countries is not fulfilling its mission appropriately [13]. On the whole, the relationship consistently tended in the direction that believers in psi have lower critical thinking ability, but only with moderate effect size, depending on measures and conceptual foundation.…”
Section: Introductionmentioning
confidence: 99%